Coaching psychology for learning facilitating growth in education - Wang, Qing 1985- (Routledge, 2018)
It will appeal to coaches and coaching psychologists, including those in training and at postgraduate level, as well as professionals in educational settings, such as school leaders, counsellors and coaches, and educational psychologists."--Provided by publisher
Keywords: Educational psychology; Counseling psychology; Personal coaching; Learning